Interferensi Sintaksis Bahasa Indonesia pada Karangan Bahasa Inggris Mahasiswa Program Studi Pendidikan Bahasa Inggris STAIN Samarinda - Bahrani Bahrani (Dinamika Ilmu, 2009)
English is the second language that has to be learned in formal education institution and also becomes compulsory subject for students of English department. Each language has different elements that make the students are difficult to master foreign language (English). Moreover, language mastery must have four language skills where composition is one of skills in language. This article explains the result of the research concerns with the Indonesian language syntactical interference on English essay. Based on the result of the research, the ability of writing sentences on English essay is still influenced by Indonesian language, even thought many students are able to write English essay with the appropriate grammar especially for the students of English Department of the fourth semester at State Institute of Islamic Studies Samarinda.